The role of the mussel Mytilus spp. in the transmission of ostreid herpesvirus-1 microVar. Issue 8 (21st December 2017) - O' Reilly, A. J.; Laide, C.; Maloy, A; Hutton, S.; Bookelaar, B.; O' Sullivan, K.; Lynch, S. A.; Culloty, S. C.
Abstract: The Pacific oyster Crassostrea gigas contributes significantly to global aquaculture; however, C. gigas culture has been affected by ostreid herpesvirus-1 (OsHV-1) and variants. The dynamics of how the virus maintains itself at culture sites is unclear and the role of carriers, reservoirs or hosts is unknown. Both wild and cultured mussels Mytilus spp. ( Mytilus edulis, Mytilus galloprovincialis and hybrids) are commonly found at C. gigas culture sites. The objective of this study was to investigate if Mytilus spp. can harbour the virus and if viral transmission can occur between mussels and oysters. Mytilus spp. living at oyster trestles, 400–500 m higher up the shore from the trestles and up to 26 km at non-culture sites were screened for OsHV-1 and variants by all the World Organization for Animal Health (OIE) recommended diagnostic methods including polymerase chain reaction (PCR), quantitative PCR (qPCR), histology, in situ hybridization and confirmation using direct sequencing. The particular primers that target OsHV-1 and variants, including OsHV-1 microVar ( μ Var), were used in the PCR and qPCR. OsHV-1 μ Var was detected in wild Mytilus spp. at C. gigas culture sites and more significantly the virus was detected in mussels at non-culture sites. Cohabitation of exposed wild mussels and naïve C. gigas resulted in viral transmission after 14 days, under an elevated temperature regime. These results indicate that mussels can harbour OsHV-1 μ Var; however, the impact of OsHV-1 μ Var on Mytilus spp. requires further investigation.